Revisiting Classical Exegesis on Nushūz in the Qur’an and Its Relevance to Contemporary Domestic Violence in Indonesia - Fatah, Abdul; Karim, Abdul; Waro, Mochamad Tholib Khoiril (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
This study re-examines the classical interpretations of nushūz and ḍaraba found in QS. An-Nisā’ [4]:34, 128 and explores their relevance to domestic violence issues in Indonesia. The research method that was employed is a literature study that explores the words nushūz and wadribū (ḍaraba: to hit) in QS. An-Nisā'[4]:34 and 128 through the commentaries of al-Ṭabarī, al- Qurṭubī, and Ibn Kathīr from the perspective of gender equality. The findings indicate that al-Ṭabarī views nushūz as a wife’s arrogance, al-Qurṭubī interprets it as animosity between spouses, and Ibn Kathīr regards it as the wife neglecting her obligations. In QS. An-Nisā’ [4]:128, nushūz is understood as the husband’s negligence or withdrawal from his wife. Meanwhile, waḍribūhunna in QS. An-Nisā’ [4]:34 is interpreted by al-Ṭabarī as a non-harmful physical measure, by al-Qurṭubī as a light, corrective action, and by Ibn Kathīr as a blow that causes no injury. Although these classical interpretations often depict the wife as the erring party and the husband as being in the right—a stance that risks perpetuating unequal power dynamics—the Qur’an itself underscores the principle of equality between men and women. In this light, nushūz should apply to both spouses, reflecting the possibility that either partner could be at fault. Al-Qurṭubī’s understanding of nushūz as mutual hatred is more compatible with notions of gender equity. Additionally, interpreting ḍaraba as “offering guidance” or “providing a positive example” is more appropriate than viewing it as a physical strike, which can escalate into domestic violence. This reinterpretation, therefore, holds promise for fostering more equitable marital relationships in contemporary society.